Gastrointestinal sequelae after surgery for necrotising enterocolitis: a systematic review and meta-analysis. Issue 3 (26th May 2019) - Hau, Eva-Maria; Meyer, Sarah C; Berger, Steffen; Goutaki, Myrofora; Kordasz, Marcin; Kessler, Ulf
Abstract : Objectives: To document what types of gastrointestinal sequelae were described after surgery for necrotising enterocolitis (NEC) and to analyse their frequency. Design: Systematic review and meta-analysis. Data sources: Medline, EMBASE and the Cochrane library (CENTRAL) from 1990 to October 2016. Eligibility criteria for selecting studies: We included studies, which provided original data on the occurrence of gastrointestinal sequelae in patients surviving surgery for NEC. Meta-analysis and metaregression to assess heterogeneity were performed for studies including 10 or more patients with gastrointestinal strictures, recurrence of NEC, intestinal failure (IF) and adhesion ileus. Results: Altogether 58 studies, including 4260 patients, met the inclusion criteria. Strictures were reported to occur in 24% (95% CI 17% to 31%) of surviving patients, recurrence of NEC in 8% (95% CI 3% to 15%), IF in 13% (95% CI 7% to 19%) and adhesion ileus in 6% (95% CI 4% to 9%). Strictures were more common following enterostomy (30%; 95% CI 23% to 37%) than after primary anastomosis (8%; 95% CI 0% to 23%) and occurred more often after enterostomy without bowel resection than with bowel resection. We found considerable heterogeneity in the weighted average frequency of all sequelae (I 2 range: 38%–90%). Intestinal outcomes were poorly defined, there were important differences in study populations and designs, and the reported findings bear a substantial risk of bias. Conclusions: Gastrointestinal sequelae in neonates surviving surgery for NEC are frequent. Long-term follow-up assessing defined gastrointestinal outcomes is warranted.